Working in poverty: Informal employment of household gardeners in Eastern Cape towns, South Africa. Issue 6 (2nd November 2022) - King, A.; Shackleton, C. M.
ABSTRACT: In South Africa there has been relatively little consideration of the informal employment offered to domestic household workers and gardeners. Here we report on the number and profile of gardeners employed by private households and the wage and satisfaction rates in 12 towns of the Eastern Cape. Over 98% of the informal gardeners were male, middle-aged and with limited formal schooling. Approximately 58% of middle and upper income households employed a gardener, at a mean daily rate of R112.20 in 2019. This equated to 13 170 gardeners earning a total wage bill of R139 million p.a. across the 12 towns, which scales up to 0.7–1 million informal gardeners nationally earning approximately R10–14 billion per year. However, daily remuneration was insufficient to cover basic needs, and slightly more than half of the gardeners would prefer a different job, indicating the survivalist nature of the sector.